Case report: Teflon granuloma following microvascular decompression manifesting as light-triggered trigeminal neuralgia - Prasetya, Mustaqim; Adidharma, Peter; Inoue, Takuro; Sulistyanto, Adi; Fadhil,; Oswari, Selfy; Keswani, Ryan Rhiveldi; Kusdiansah, Muhammad; Aji, Yunus Kuntawi; Arham, Abrar (Frontiers in Surgery, 2022)
Trigeminal Neuralgia is commonly triggered by stimuli in the area of the trigeminal nerve innervation. We report an exceptionally rare case of a 61-year-old woman who complained of recurrent trigeminal neuralgia, which sole trigger was seeing a bright light. Teflon felt that was placed on the nerve root in the initial surgery was suspected of causing this rare type of trigeminal neuralgia. A reflex circuit linking luminance to trigeminal nerve activity may be implicated in activating a trigeminal nociceptive pathway by a bright light trigger.